KNOEVENAGEL CONDENSATION OF 5-SUBSTITUTED FURAN-2-CARBOXALDEHYDE WITH INDAN-1,3-DIONE - Khalaf, Muna; Abdel-Wahab, Abdo; Kandil, Farouk (Iraqi Journal of Science, 2024)
A series of new heterocyclic compounds of2-(5-substituted -Furfurylidene)-Indane-1,3-dione, were prepared and identified by their melting points, Infrared,Ultraviolate, and Nuclear magnetic resonance spectrua.